Enduring Violence: The Postwar Struggles in East-Central Europe, 1917–21. (January 2015) - Böhler, Jochen
In East-Central Europe, the First World War did not end with the armistices of 1918. In the wake of the Russian Revolution and imperial collapse, armed conflicts of various kinds, sizes, and political motivation dominated the years 1917 to 1922, when former citizens of the major European land empires fought for independence and statehood. These conflicts were not only rooted in pre-war conflicts, and in growing tensions between the awakening national self-consciousness of the indigenous populations on the one hand and the sometimes harsh imperial politics of the nineteenth and early twentieth century on the other. With the imperial armies dissolving, a brutal but in some ways conventional war – occasional and sometimes even large-scale atrocities against civilians notwithstanding – gave way to an outburst of paramilitary violence against civilians. Various warlords in the western territories of former Tsarist Empire used violence as a mere raison d'etre; armies under development – as the Polish army or the Bolshevik Red Guard/Army – lacked discipline, their conscripts being brutalized and inclined to commit atrocities. Ultra-violent milieus such as the European counterrevolutionary militias added to the extraordinary death toll in the region.